Local time asymmetries of SSC-associated hydromagnetic variations at the geosynchronous altitude - Kuwashima, Masayuki; Fukunishi, Hiroshi (1985)
P(論文) 167 SSC events have been studied by using the data observed at the multiple satellites at the geosynchronous altitude. The strong local time asymmetry of the SSC amplitude which was found by KOKUBUN (J. Geophys. Res., 88,10025,1983) has been confirmed. The pronounced local time asymmetry has also been found with the direction of the initial movement of Psc magnetic pulsations. Those local time effects are interpreted by the intensification of the magnetopause surface current during an SSC event, and by the distance between the geosynchronous satallite and the surface current. It has also been clarified that the SSC signal propagates with a speed of 400-700km/s across the field lines in the magnetosphere as suggested by WILKEN et al. (J. Geophys. Res., 87,5901,1982). departmental bulletin paper